2022
DOI: 10.17219/acem/147271
|View full text |Cite
|
Sign up to set email alerts
|

RPS27 selectively regulates the expression and alternative splicing of inflammatory and immune response genes in thyroid cancer cells

Abstract: RPS27 selectively regulates the expression and alternative splicing of inflammatory and immune response genes in thyroid cancer cells [published online as ahead of print on May 12, 2022].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…RPS27 , as a specifical gene identified by mRMR, has been widely reported to be a housekeeping gene in the colon [ 75 ]. However, further studies showed that during pathological immune activation, RPS27 has shown to be abnormally regulated [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPS27 , as a specifical gene identified by mRMR, has been widely reported to be a housekeeping gene in the colon [ 75 ]. However, further studies showed that during pathological immune activation, RPS27 has shown to be abnormally regulated [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…RPS27 , as a specifical gene identified by mRMR, has been widely reported to be a housekeeping gene in the colon [ 75 ]. However, further studies showed that during pathological immune activation, RPS27 has shown to be abnormally regulated [ 75 ]. Therefore, such a gene may help recognize activated immune cells from our candidates, including plasma B cells and activated CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%